Does flood affect property values? a hedonic analysis of residential property values in Peninsular Malaysia - Ismail, Nur Hafizah; Abd Karim, Mohd Zaini; Basri, Bakti Hasan (Institute for Management and Business Research (IMBRe), Universiti Utara Malaysia, 2014)
The hedonic pricing model (HPM) has been used to identify the values of residential property due to flood impact.Most of the previous studies had been conducted using flood frequency and flood depth to measure flood variables rather than flood duration.The hedonic pricing study presented here investigated the effect of flood duration on residential property value in Peninsular Malaysia. We measured the housing attributes involving location, structural, and neighborhood attributes. We also developed the interaction variable between flood and structural attributes to determine whether the effect of flood duration on residential property value differs across house age, size of land area, and number of bedroom. The results suggest that the sale price of residential property is significantly decreased by 0.015 percent due to flood.